2021
DOI: 10.1111/jch.14341
|View full text |Cite
|
Sign up to set email alerts
|

Home blood pressure telemonitoring for improving blood pressure control in middle‐aged and elderly patients with hypertension

Abstract: The blood pressure (BP) control rate among treated hypertensives in China remains low at 37.5%. The relationship between home blood pressure telemonitoring (HBPT) and BP control is controversial. The authors aimed to investigate the relationship between HBPT and BP control in middle‐aged and elderly hypertensives. In total, 252 hypertension patients aged between 60 and 79 years were enrolled. The patients were given either HBPT through interactive platforms between physicians and patients (telemonitoring group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Telemonitoring also has considerable utility in the home management of frail patients with multiple chronic diseases [59,60]. In this setting, the concomitant presence of cognitive or visual impairment might complicate the use of digital tools.…”
Section: Tailoring Digital Health Interventions To Overcome Potential...mentioning
confidence: 99%
See 1 more Smart Citation
“…Telemonitoring also has considerable utility in the home management of frail patients with multiple chronic diseases [59,60]. In this setting, the concomitant presence of cognitive or visual impairment might complicate the use of digital tools.…”
Section: Tailoring Digital Health Interventions To Overcome Potential...mentioning
confidence: 99%
“…However, such barriers can be overcome using devices tailored to the patient's clinical conditions and digital skills. For example, in patients unable to use e-mails or other ICT platforms, physicians can use telemonitoring systems that directly transfer home-acquired BP values to the patient's clinical records, minimizing patient involvement [60]. Similarly, video supports, voice assistants or smart speaker technologies embedded in remote BP monitoring systems can guide patients with cognitive or visual impairment on the correct use of the devices [61][62][63].…”
Section: Tailoring Digital Health Interventions To Overcome Potential...mentioning
confidence: 99%
“…65) participants [31], though older participants have been captured alongside middle-aged and younger participants with hypertension. Some of these trials enrolling predominantly older participants showed that telemonitoring and case management was effective [35][36][37], while others have shown reduced effectiveness in subgroup analyses of older participants [21][22][23]. The limited evidence and variability of outcomes demonstrate a need to examine older subjects as a distinct population, for whom additional considerations may apply when attempting to improve BP control.…”
Section: ããmentioning
confidence: 99%
“…Some previous studies of telemonitored HBPM and case management appear to show worse effectiveness in subgroup analyses of older adults compared to middle-aged adults [21][22][23]. BP reduction alone is also not the sole objective in older adults; in cases where hypotension or other adverse effects occur, deprescribing of anti-hypertensive agents is also important [14,24].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, middle-aged and older patients with hypertension under standardized management by the Hypertension Research Institute of the Second Affiliated Hospital of Baotou Medical College used intelligent sphygmomanometers to monitor their blood pressure and smartphone apps to monitor and manage their blood pressure. After 12 months, the systolic blood pressure (SBP) and diastolic blood pressure (DBP) of the patients significantly decreased ( P <.001) [ 22 ]. Sun et al [ 23 ] used the remote “Internet plus” internet-based management mode to intervene in older patients with hypertension aged ≥60 years for 6 months.…”
Section: Introductionmentioning
confidence: 99%